First-order planar autoregressive model - Sergiy Shklyar (Modern Stochastics: Theory and Applications)
This paper establishes the conditions for the existence of a stationary solution to the first-order autoregressive equation on a plane as well as properties of the stationary solution. The first-order autoregressive model on a plane is defined by the equation